Indoleamine 2,3-Dioxygenase Activity in Chlamydia muridarum and Chlamydia pneumoniae Infected Mouse Lung Tissues - Virok, Dezső P.; Raffai, Tímea; Kókai, Dávid; Paróczai, Dóra; Bogdanov, Anita; Veres, Gábor; Vécsei, László; Poliska, Szilárd; Tiszlavicz, László; Somogyvári, Ferenc; Endrész, Valéria; Burián, Katalin (Frontiers in Cellular and Infection Microbiology, 2019)
Chlamydia trachomatis infections are the most prevalent sexually transmitted infections with potentially debilitating sequelae, such as infertility. Mouse models are generally used for vaccine development, to study the immune response and histopathology associated with Chlamydia infection. An important question regarding murine models is the in vivo identification of murine host genes responsible for the elimination of the murine and human Chlamydia strains. RNA sequencing of the Chlamydia muridarum infected BALB/c lung transcriptome revealed that several genes with direct antichlamydial functions were induced at the tissue level, including the already described and novel members of the murine interferon-inducible GTPase family, the CXCL chemokines CXCL9, CXCL11, immunoresponsive gene 1, nitric oxide synthase-2 (iNOS) and lipocalin-2. Indoleamine 2,3-dioxygenase 1-2 (IDO1-2) previously described potent antichlamydial host enzymes were also highly expressed in the infected murine lungs. This finding was novel, since IDO was considered as a unique human antichlamydial defense gene. Besides a lower level of epithelial cell positivity, immunohistochemistry showed that IDO1-2 proteins were expressed prominently in macrophages. Detection of the tryptophan degradation product kynurenine and the impact of IDO inhibition on Chlamydia muridarum growth proved that the IDO1-2 proteins were functionally active. IDO1-2 activity also increased in Chlamydia muridarum infected C57BL/6 lung tissues, indicating that this phenomenon is not mouse strain specific. Our study shows that the murine antichlamydial response includes a variety of highly up-regulated defense genes in vivo. Among these genes the antichlamydial effectors IDO1-2 were identified. The potential impact of murine IDO1-2 expression on Chlamydia propagation needs further investigation.